14‐3‐3 in Thoracic Aortic Aneurysms: Identification of a Novel Autoantigen in Large Vessel Vasculitis. Issue 7 (July 2015) - Chakravarti, Ritu; Gupta, Karishma; Swain, Mamuni; Willard, Belinda; Scholtz, Jaclyn; Svensson, Lars G.; Roselli, Eric E.; Pettersson, Gosta; Johnston, Douglas R.; Soltesz, Edward G.; Yamashita, Michifumi; Stuehr, Dennis; et al.
<x xml:space="preserve">Abstract</x> Objective Large vessel vasculitides (LVV) are a group of autoimmune diseases characterized by injury to and anatomic modifications of large vessels, including the aorta and its branch vessels. Disease etiology is unknown. This study was undertaken to identify antigen targets within affected vessel walls in aortic root, ascending aorta, and aortic arch surgical specimens from patients with LVV, including giant cell arteritis, Takayasu arteritis, and isolated focal aortitis. Methods Thoracic aortic aneurysm specimens and autologous blood were acquired from consenting patients who underwent aorta reconstruction procedures. Aorta proteins were extracted from both patients with LVV and age‐, race‐, and sex‐matched disease controls with noninflammatory aneurysms. A total of 108 serum samples from patients with LVV, matched controls, and controls with antinuclear antibodies, different forms of vasculitis, or sepsis were tested. Results Evaluation of 108 serum samples and 22 aortic tissue specimens showed that 78% of patients with LVV produced antibodies to 14‐3‐3 proteins in the aortic wall (93.7% specificity), whereas controls were less likely to do so (6.7% produced antibodies). LVV patient sera contained autoantibody sufficient to immunoprecipitate 14‐3‐3 protein(s) from aortic lysates. Three of 7 isoforms of 14‐3‐3 were found to be up‐regulated in aorta specimens from patients with LVV, and 2 isoforms (ε and ζ) were found to be antigenic in LVV. Conclusion This is the first study to use sterile, snap‐frozen thoracic aorta biopsy specimens to identify autoantigens in LVV. Our findings indicate that 78% of patients with LVV have antibody reactivity to 14‐3‐3 protein(s). The precise role of these antibodies and 14‐3‐3 proteins in LVV pathogenesis deserves further study.